Wood Craft Projects - Carrick, Graham (Rourke Enterprises, Inc. Vero Beach, Florida, 1990)
Details how to make a variety of prjects by constructing and carving wood.
Includes index.
8 - 10 years
Keywords: Woodwork; Handicraft